PERANAN BALANCED SCORECARD SEBAGAI ALTERNATIF SISTEM MANAJEMEN STRATEGIS PONTREN - Sari Widati; Ardian Prima Putra; Gustita Arnawati Putri (STIE Atma Bhakti, 2018)
The purpose of this research is to find empirical evidence related to the role of balanced scorecard which is used as alternative strategic management system of boarding school. Salafiyah, khalafiyah and modern boarding school serve as sample in this research with random sampling sample selection system. The case study was used as a research method by conducting unstructured interviews and direct observation. The results show that in principle BSC map strategy attributes can be applied in all boarding school, however not all types of boarding school can respond quickly but need to make some adjustments. Modern boarding school most quickly apply the attributes of the BSC's map strategy, khalafiyah boarding school can apply with some adjustments and salafiyah boarding school has not applied at all but interested to make improvements of strategic management system boarding school so that BSC serve as an alternative strategic management system boading school.